Safety and efficacy of sofosbuvir plus velpatasvir with or without ribavirin for chronic hepatitis C virus infection: A systematic review and meta-analysis - Hussien Ahmed; Abdelrahman I. Abushouk; Attia Attia; Mohamed Gadelkarim; Mohamed Gabr; Ahmed Negida; Mohamed M. Abdel-Daim (Elsevier, 2018)
Velpatasvir is a newly FDA-approved inhibitor of hepatitis C virus (HCV) NS5A protein. We performed this systematic review and meta-analysis to investigate the safety and efficacy of velpatasvir plus sofosbuvir in the treatment of chronic HCV infection. A computerized literature search of PubMed, SCOPUS, EMBASE, EBSCO, Web of science, and Cochrane CENTRAL was conducted using relevant keywords. Data from eligible studies were pooled in a fixed effect meta-analysis model, using OpenMeta[Analyst] software. Pooled data from six randomized trials (n = 1427 patients) showed that velpatasvir plus sofosbuvir achieved sustained virological response (SVR12) rates of 98.2% in genotype-1, 99.4% in genotype-2, 94.7% in genotype-3, 99.6% in genotype-4, 97.1% in genotype-5, and 98.8% in genotype-6 patients. The addition of ribavirin did not significantly increase the SVR12 (RR = 0.95, 95%CI [0.88, 1.02]) or decrease relapse rates (RR = 2.52, 95% CI [0.49, 12.87]) in HCV genotype-1 patients. However, adding ribavirin significantly increased SVR12 (RR = 89.5, 95% CI [80.4, 99.5]) in genotype-3 patients. In conclusion, the 12-week regimen of sofosbuvir plus velpatasvir was highly effective in HCV patients, including those with cirrhosis and former treatment experience. Except for genotype-3, adding ribavirin was not associated with significant improvements in SVR12 rates. Further studies should investigate the effect of adding ribavirin to this regimen, especially in HCV genotype-3 patients. Keywords: Sofosbuvir, Velpatasvir, Ribavirin, Hepatitis C Virus, Meta-analysis